Endophytic potential of Beauveria bassiana (Bals.-Criv.) Vuill against sap-sucking insect pests in kiwi trees and cotton plants - Papantzikos, Vasileios; Mantzoukas, Spiridon; Patakioutas, George (Journal of Plant Protection Research, 2026)
Beauveria bassiana has proven to be an efficient crop colonizer regarding its highly entomopathogenic effect against a wide range of sucking pests. In this work, two different application methods of B. bassiana (Bals.-Criv.) were studied over two years. In one case, the strain (PPRI5339) was introduced as a coating on cotton seeds (A) and applied via syringe inoculation to the kiwi tree trunk (B). In the control (C) treatments of each case, untreated plants were used. The sucking insects Aphis gossypii (Glover) on cotton plants and Halyomorpha halys (Stål) on kiwi trees were counted, and the total chlorophyll content and leaf area were also measured. The presence of B. bassiana not only reduced the population of sucking pests but also enhanced the total chlorophyll content and the leaf area in both crops. The results of these application methods are promising, encouraging the potential of this strain for further study as an environmentally friendly method against sucking pests that highly impair agricultural production.